Answer:
[tex]\kappa = \frac{\cos \theta -1}{\left[2\cdot (1 - \cos \theta) \right]^{\frac{3}{2} }}[/tex]
Step-by-step explanation:
The first and second derivatives of the components of the parametric curve are:
[tex]\dot x = 1 - \cos \theta[/tex] and [tex]\ddot x = \sin \theta[/tex]
[tex]\dot y = \sin \theta[/tex] and [tex]\ddot y = \cos \theta[/tex]
After substitution, the equation of curvature is:
[tex]\kappa = \frac{(1-\cos\theta)\cdot (\cos \theta)-\sin^{2} \theta}{\left[(1-\cos\theta)^{2}+\sin^{2}\theta \right]^{\frac{3}{2} }}[/tex]
[tex]\kappa = \frac{\cos \theta -1}{\left[2\cdot (1 - \cos \theta) \right]^{\frac{3}{2} }}[/tex]